Meniscus cell lysate induces mitochondrial dysfunction of fibroblast-like synoviocytes via upregulating ANT3 in osteoarthritis: aNT3 is a potentially important novel mediator and drug target in osteoarthritis. Issue 4 (11th April 2023) - Du, Xue; Jiang, Zongrui; Fang, Guibin; Liu, Ruonan; Wen, Xingzhao; Wu, Yinjuan; Hu, Shu; Zhang, Zhiqi
Abstract : Aims: This study aimed to investigate the role and mechanism of meniscal cell lysate (MCL) in fibroblast-like synoviocytes (FLSs) and osteoarthritis (OA). Methods: Meniscus and synovial tissue were collected from 14 patients with and without OA. MCL and FLS proteins were extracted and analyzed by liquid chromatography‒mass spectrometry (LC‒MS). The roles of MCL and adenine nucleotide translocase 3 (ANT3) in FLSs were examined by enzyme-linked immunosorbent assay (ELISA), flow cytometry, immunofluorescence, and transmission electron microscopy. Histological analysis was performed to determine ANT3 expression levels in a male mouse model. Results: We discovered for the first time that MCL was substantially enriched in the synovial fluid of OA patients and promoted the release of inflammatory cytokines from FLSs through MCL phagocytosis. Through LC‒MS, ANT3 was identified and determined to be significantly upregulated in MCL and OA-FLSs, corresponding to impaired mitochondrial function and cell viability in OA-FLSs. Mitochondrial homeostasis was restored by ANT3 suppression, thereby alleviating synovial inflammation. Furthermore, elevated ANT3 levels inhibited ERK phosphorylation. Specifically, silencing ANT3 prevented inhibition of ERK phosphorylation and significantly reduced the elevation of reactive oxygen species (ROS) and JC1 membrane potential in MCL-induced synovial inflammation. Conclusion: This study revealed the important roles of MCL and ANT3 in FLS mitochondria. Silencing ANT3 rescued ERK phosphorylation, thereby restoring mitochondrial homeostasis in FLSs and alleviating synovitis and OA development, offering a potential target for treating synovitis and preventing early-stage OA. Cite this article: Bone Joint Res 2023;12(4):274–284.